Rapid Warming Over East Antarctica Since the 1940s Caused by Increasing Influence of El Niño Southern Oscillation and Southern Annular Mode - Ejaz, Tariq; Rahaman, Waliur; Laluraj, C. M.; Mahalinganathan, K.; Thamban, Meloth (Frontiers in Earth Science, 2022)
El Niño Southern Oscillation (ENSO), Interdecadal Pacific Oscillations (IPO), and their phase relation with Southern Annular Mode (SAM) largely control Antarctic climate variability. The relative roles of these climate modes remain elusive, particularly in the backdrop of global warming. Here, we present a seasonally resolved new ice core (IND33) record of oxygen isotope (18O) for the past two centuries (1809–2013 CE) from coastal Dronning Maud Land (DML) to investigate the role of these climate modes on the Antarctic temperature variability and trend. Our investigation based on this record combined with available records from the DML region reveals that ~32% variability in 18O records is related to late spring to summer (Nov-Dec-Jan) temperature rather than the mean annual temperature. This indicates that reconstructed annual temperature based on Antarctic ice core 18O records could be biased towards the temperature of the months/seasons of higher precipitation with low-moderate wind speed, which are suitable for better preservation of ice core signal. We have reconstructed DML temperature record of the past two centuries (18092019 CE) at an annual resolution based on 18O ice core record (18091993 CE) combined with the recent ERA5 surface air temperature record (19942019 CE). The reconstructed temperature anomaly record reveals a significant cooling trend in the 19th century during 18091907 CE with a rate of 0.164  0.045 °C decade-1 followed by a warming trend from the mid-20th to early 21st centuries (19422019 CE) with a rate of 0.452  0.056 °C decade-1. This long-term warming trend since the 1940s coincides with the increase in ENSO events and its strong anti-phase relation with SAM, suggesting an increasing influence of SAM-ENSO coupling in modulating the DML temperature in the recent decades.